Analisis Perbandingan Rasio Profitabilitas Pada PT. Mulia Boga Raya Tbk (Keju) Dan PT. Ultrajaya Milk Industry & Trading Company Tbk (ULTJ) Yang Terdaftar di bursa Efek Indonesia (BEI) Priode 2020-2024 - Nurholisah Nurholisah; Abdul Rauf Chaerudin; Risma Eka Desiyani (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
The food and beverage industry in Indonesia makes a significant contribution to the national economy, with a growth rate of 4.90% in 2023. This growth is accompanied by variations in profitability among companies. PT Mulia Boga Raya Tbk (KEJU) and PT Ultrajaya Milk Industry & Trading Company Tbk (ULTJ) are two listed companies that have shown different financial performances in recent years. This study aims to analyze and compare the profitability ratios of Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) of the two companies during the 2020–2024 period. The research employs a quantitative comparative method with a descriptive case study approach, based on financial reports published by the Indonesia Stock Exchange (IDX), supported by literature study. The findings indicate that ULTJ consistently outperforms in GPM and NPM, reflecting more efficient cost and operational management. KEJU initially showed better performance in ROA and ROE but experienced a decline before improving again in 2024. These results emphasize the importance of cost, asset, and equity management in maintaining long-term profitability. In conclusion, ULTJ demonstrates greater stability in profitability, while KEJU needs to enhance efficiency to remain competitive. These findings are expected to serve as practical references for management and investors in making strategic decisions within the food and beverage industry.